SUSTAINING THE STRIDE OF HEALTH AGENDA BEYOND 2015 IN POST MDGS SCENARIO: A PROJECTED ROADMAP FOR THE DEVELOPING COUNTRIES - Shaikh, Babar Tasneem (Journal of Ayub Medical College Abbottabad, 2014)
As the world is reaching toward 2015, the echoes of MDGs are becoming louder. Results with regard to achievements of the targets set globally, show mixed results. Very understandably, the developing countries will miss most of the targets by far, and the attributed reasons are obvious. Dearth of resources-financial and human, evidence for decision making, infrastructure, meaningful collaboration with developed countries, and overall governance of the health sector are some of the pitfalls on 2000-2015 screen. Nonetheless, international commitments are sending positive vibes and message that glass is half full. Countries must keep the pace and sustain the stride of MDGs agenda, with an appraised roadmap, of course. Poverty, natural and man-made disasters, and slow socio-economic development, and some incongruous technologies are the challenges en route. A holistic approach is the need of the time, and therefore this paper presents a strategic framework drawn from the WHO's proposed health systems building blocks, which might help the developing countries and fragile health systems to turn around the state of affairs